2007
DOI: 10.1007/s11071-006-9183-0
|View full text |Cite
|
Sign up to set email alerts
|

Time and frequency domain nonlinear system characterization for mechanical fault identification

Abstract: Mechanical systems are often nonlinear with nonlinear components and nonlinear connections, and mechanical damage frequently causes changes in the nonlinear characteristics of mechanical systems, e.g. loosening of bolts increases Coulomb friction nonlinearity. Consequently, methods which characterize the nonlinear behavior of mechanical systems are wellsuited to detect such damage. This paper presents passive time and frequency domain methods that exploit the changes in the nonlinear behavior of a mechanical s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…This method attempts to obtain a minimum-effort diagnosis of damage and despite requiring significant numbers of sensors, similar approaches could be considered in the future. For instance, progress was made towards detecting damage by analyzing the non-linear response of an automobile suspension system to entirely unknown inputs using a relatively simple model of the overall system 22 .…”
Section: Model-based Methodsmentioning
confidence: 99%
“…This method attempts to obtain a minimum-effort diagnosis of damage and despite requiring significant numbers of sensors, similar approaches could be considered in the future. For instance, progress was made towards detecting damage by analyzing the non-linear response of an automobile suspension system to entirely unknown inputs using a relatively simple model of the overall system 22 .…”
Section: Model-based Methodsmentioning
confidence: 99%
“…There have been some works in that direction, but never for damage classification or quantification purposes. In a linear framework, some authors [19,20] have shown that a nonlinear damage will impact the transmissibility functions (i.e. the frequency domain ratio between two different outputs of the system) and they used such information to detect and locate the damage.…”
Section: Introductionmentioning
confidence: 99%
“…1 In the early study, research of mechanical fault diagnosis is mainly focused on time domain analysis and frequency domain analysis. 2 The time domain analysis is based on statistical characteristics and dimensionless parameters, such as maximum value, peak-to-peak value, kurtosis factor, and so on. 3 Because of colossal uncorrelated signals' interference, such as sensor noise and the external disturbances, mechanical fault signals cannot be observed directly through time domain analysis.…”
Section: Introductionmentioning
confidence: 99%